A survey of violence and vulgarity in children television programs: a content analysis, and assessment of perceptions of parents and children (ViCTiM study) - Ashraf Jahangeer; Manahil Akmal; Bushra Perveen; Maaz Bin Nazir; Faryal Mustafa; Bilal Ahmed Khan; Hafsa Jabeen; Nighat Mirza; Hajra Ejaz Khilji (Journal of the Pakistan Medical Association, 2021)
Abstract Objectives: To quantify the depiction of violence and vulgarity in television programmes for children, and to assess the perception and practices of parents and children about television programmes meant for children. Methods: We conducted this mixed-methods cross-sectional study in Karachi, Pakistan in the months of August-September 2018, after approval from the ethics review board of Dow University of Health Sciences, Karachi. First, a content analysis of over 102 hours of various television programmes meant for children was performed in the light of the guidelines set out by the World Health Organisation, the United States Federal Communication Commission and the Pakistan Electronic Media Regulatory Authority. Seven trained researchers sampled the children prime time throughout a week, including the weekends, using a structured tally sheet. Subsequently, interviews were conducted with dyad of parent-children from the employees’ list of a public-sector university. A questionnaire was also administered to assess the practices and perceptions of the parents-children dyad about the programmes. Data was analysed using SPSS 24. Results: Of the 173 subjects, 84(48.6%) were parents and 89(51.4%) were children. The mean age of the children was 89 children 9.8±3.7 years. Content analysis comprised 6130 minutes, of which 5442(88.8%) had depictions of violence and vulgarity. Depiction of violence and vulgarity was prevalent on television channels that were watched the most, but there was no significant difference in this regard (p=0.238). Of the parents, 68(81%) expressed concern over the effect of screen time and content on the mental health of their children.